Determinan Perawatan Kaki pada Lansia Diabetes di Kabupaten Bondowoso - Dewi, Sofia Rhosma; Sasmiyanto; Pratama, Eric; Wardhani, Annisa Eka Adhitya (Universitas Muhammadiyah Jember, 2023)
Diabetes mellitus is one of chronic disease in elderly. Diabetic elderly needs to do foot care to prevent diabetic ulcer. The aging process has an impact on foot care performed by diabetic elderly. The purpose of this study was to identify the determinants of foot care in diabetic elderly in Bondowoso. It’s a correlational study conducted with cross sectional approach. It’s involved 69 respondents taken by consecutive sampling from total 74 elderly who underwent treatment at Holistic Care Clinic Bondowoso. The data was taken by using DKQ, FCCS, Lawton IADL, family support questionnaire, and NAFF. The data were analysed using multiple logistic regression test. The results show 4 predictor of foot care implementation in diabetic elderly which are access to information about diabetes mellitus complications (OR = 1,79; 95% CI 0,626 – 5,131); knowledge about diabetes mellitus (OR = 2,08; 95%CI 0,750 – 5,769); family support (OR = 2,159; 95%CI = 0,775 – 6,011) and independence in implementing IADL (OR = 0,376; 95%cI = 0,135 – 1,044). Diabetic elderly need family support to ensure proper foot care. Key words: elderly, diabetes mellitus, foot care